Enhancing Sustainable Agricultural Land Protection Through Community Engagement: A Case Study of Malang Regency, Indonesia - Rofiq, Ainur; syafaat, Rahmad; Afandhi, Aminuddin (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
This study examines the dynamics of sustainable agricultural land protection in Malang Regency, Indonesia, focusing on the institutional integration of community participation in controlling land-use conversion. Rapid urbanization has intensified pressure on agricultural zones, challenging food security and ecological sustainability. Despite the presence of national and local legal frameworks such as Law No. 41/2009 and Regional Regulation No. 6/2015, the implementation of land protection remains weak due to limited inter-agency coordination, regulatory fragmentation, and marginal public involvement. This research employed a qualitative approach using literature review, semi-structured interviews, focus group discussions, and NVivo-assisted thematic coding to analyze institutional practices and community perceptions. Findings reveal that community participation is largely informal and reactive, lacking formalized channels in spatial planning processes. The absence of inclusive governance mechanisms has reduced regulatory legitimacy and effectiveness. A proposed hierarchical model advocates for legislative reform, institutionalized participatory procedures, and targeted capacity-building as integrated strategies to strengthen land governance. The study concludes that participatory approaches embedded within legal and institutional systems enhance policy effectiveness and provide a viable framework for replicating sustainable land-use governance in regions facing similar socio-political constraints.